Administrative and legal regulators of compliance with social and labor rights of citizens in the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2022)
The article is devoted to the issues of correlation, interrelation and interdependence of the legal regulators of administrative law and the socio-labor legal block, that is, labor law and social security law. The peculiarity of regulatory administrative functions lies in their managerial functionality, which cannot but affect virtually all branches of Kazakh law, which is why administrative law is a multi-vector, multifunctional legal regulatory mechanism. It cannot be reduced solely to a system of administrative sanctions, as is often done in the framework of industry comparison. However, not every management falls under administrative and legal relations, remaining the subject of regulation of special industry norms. The social and labor legal block is in close legal connection with the administrative one. In particular, labor law regulating labor and closely related relations between employees and employers, when regulating the labor of certain subject categories, transfers legal regulations under the sphere of influence of administrative law. We are talking, for example, about relations with civil servants, military personnel, etc. The scope of their work falls under the regulation of both labor law and administrative law. According to the same criterion, management functions themselves are classified in the pension system, social insurance, social health insurance, and labor law. It is also impossible to ignore the administrative sanctions applied when committing administrative offenses, which are often encountered when citizens exercise their social and labor rights and freedoms. The authors of the article consider the issues of the ratio of these regulatory administrative resources, mechanisms and make proposals for their improvement.Keywords: management system, pensions, migrant workers, medical care, employment contract, civil service